2012
DOI: 10.1103/physrevlett.109.093601
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Binomial Light

Abstract: The click statistics from on-off detector systems is quite different from the counting statistics of the more traditional detectors. This necessitates introduction of new parameters to characterize the nonclassicality of fields from measurements using on-off detectors. To properly replace the Mandel QM parameter, we introduce a parameter QB. A negative value represents a sub-binomial statistics. This is possible only for quantum fields, even for super-Poisson light. It eliminates the problems encountered in di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 21 publications
1
83
0
Order By: Relevance
“…However, the HBT test uses only single measurement layout among many where the nonclassicality of single photon states can manifest itself. Probably, many other linear optical (LO) schemes with single photon detectors can manifest single photon nonclassicality differently to that HBT test [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the HBT test uses only single measurement layout among many where the nonclassicality of single photon states can manifest itself. Probably, many other linear optical (LO) schemes with single photon detectors can manifest single photon nonclassicality differently to that HBT test [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…If we now assume that the multiplexing is performed with an equal splitting into the channels and each channel is detected with detectors which have equal properties, i.e., having the same detector response (quantum efficiency and dark-count rate), the Q B parameter [20],…”
Section: B Sub-binomial Parametermentioning
confidence: 99%
“…Furthermore, other multiplexing strategies such as fiber-loop detectors [11,33] by design do not provide an equal split- * martin.bohmann@ino.it † maria.chekhova@mpl.mpg.de ting. For such unequal-splitting scenarios, a condition based on second-order moments [25] has been derived as a generalization of the corresponding equal-splitting condition [20]. More general higher order criteria have, however, not yet been reported for such unequal-splitting detections.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we have shown that the binomial form requires a reformulation of nonclassicality conditions [24,28]. Moments of the click counting statistics can be used to identify quantum correlations -even between multiple detector systems.…”
Section: Heralded State Preparation With Click Detector Systemsmentioning
confidence: 99%
“…Based on the variance of these statistics, it is possible to identify in theory and experiment nonclassical, i.e. sub-binomial, light [24,25]. A source of correlated photon pairs together with the considered class of detectors can be used, for example, to identify spatial correlations [26][27][28] or to perform a detector calibration [29,30].…”
Section: Introductionmentioning
confidence: 99%